IMPROVING THE SKILL AND THE INTEREST OF WRITING ADVERTISEMENTS AND POSTERS THROUGH ESA SEQUENCE - Fatma Yuniarti, author (JURNAL SMART, 2015)
The action reserach aims at improving the studentsâ writing skill especially to write advertsements and posters. Both are the short functional texts to be learned at the second semester. According to the data on pre cycle, the students of second semester got difficulties to write advertisements and posters. A treatment was necessary to help the students overcome their problem. To consider the related literature, the writer decided to implement ESA sequence (Harmer 2001) in the class. The elements of teaching in ESA Sequence are Engage (to arouse the studentsâ interests), Study (learn the language focus), and Activate (use the language freely and communicatively). The data were taken from the test of the linguistic competence mastery, the students writing, and the questionnaire. The studentsâ linguistic competence got increased as shown by the score (58 in pre-cycle, 66 in cycle 1, and 70 in cycle 2). The studentsâ ability to write the short functional texts also get improved as indicated by the average score on writing tasks (53 in pre-cycle, 63 in cycle 1, 72 in cycle 2). The interest also gets better as shown by the score of the questionnaire (22,3 in pre-cycle, 33,5 in cycle 1, and 37 in cycle 2). It means ESA Sequence can improve the studetsâ ability to write advertisements and posters.Key words : advertisement, ESA (Engange Study Activate), poster